RESPONS PEMUDA PEDESAAN TERHADAP KEBIJAKAN PEMBANGUNAN DAERAH DALAM KETERSEDIAAN LAPANGAN KERJA - Yudhistira Saraswati; Rolan Mart Sasongko; Hafidh Rifky Adiyatna; Hesty Yuliana; Muh ivandi S (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2025)
Development inequality remains a persistent issue in many regions, often stemming from imbalanced policy implementation and regional disparities. Youth, as a socially and economically vulnerable group, are particularly affected by such conditions. This study aims to analyze the responses of young people in East Java Province to local development policies. Using a descriptive qualitative approach supported by surveys and literature review, the research explores perceptions and experiences of youth toward government-led development initiatives. The findings reveal that, overall, youth in East Java demonstrate a positive attitude toward regional development policies, acknowledging improvements in infrastructure, education, and public services. However, significant concerns remain, particularly regarding the limited and indirect impact of such policies on employment opportunities. Many young people, especially those from rural areas, express dissatisfaction with the lack of accessible jobs, which compels them to migrate to urban centers or other provinces in search of better economic prospects. This phenomenon highlights a critical gap in inclusive development planning. The study underscores the urgent need for strategic policy reforms aimed at reducing regional disparities and enhancing youth participation in local development. One recommended approach is the acceleration of development in underdeveloped areas by optimizing local potentials such as agriculture, creative industries, and rural-based manufacturing. Strengthening these sectors can not only create sustainable employment but also curb youth migration and promote balanced regional growth. The study contributes to the discourse on youth-oriented development and serves as a reference for policymakers seeking inclusive and equitable development strategies.